A biomechanical analysis of sprinters vs. distance runners at equal and maximal speeds - Bushnell, T. D. (2004)
In the sport of track and field, sprinting and distance running represent two major categories of athletes. Sprinting is associated with power and speed, whereas distance running focuses on the economy of movement. With distance running there are elements of sprint technique that overlap. With distance events, there comes a time near the end of the race where economy gives way to speed. If the distance runners knew how to alter their technique in a way to become more sprint-like, this process could possibly be more successful. PURPOSE: This study compared the differences in technique between sprinters and distance runners while running at equal and maximal speeds. METHODS: Subjects for the study consisted of 10 Division I collegiate distance runners, 10 Division I collegiate sprinters, and 10 healthy non-runners. The subjects performed two tests, with each consisting of a 60 meter run completed on the track. Test 1 was run at a pace of 5.81 m/s (4:37 min/mile), while Test 2 was completed at maximal speed. Video footage of each trial was collected at 180 Hz, monitoring hip, knee, thigh, and shank positions, as well as stride length, and contact time. RESULTS: Significant differences (p < .05) between the sprint and distance groups at maximal speed were found in the following areas: speed, minimum hip angle, knee extension at toe-off, stride length, contact time, and the position of the recovery knee at touchdown. Sprinters and distance runners exhibited a significantly lower minimum knee angle than those in the control group. Significant differences between the sprint and control group existed at the minimum hip angle, speed, stride length, contact time, and the position of the recovery knee at touchdown. Regarding the paced trial, the sprinters and distance runners showed significant difference concerning the minimum hip angle, center of mass at touchdown, and recovery knee at touchdown. Sprinters differed significantly from the control group in contact time, the center of mass at touchdown and the position of the recovery knee at touchdown. CONCLUSION: As distance runners attempt to sprint, the desired adaptations do not necessarily occur. The development of economical distance form is a fairly natural process that occurs with the miles of training. Sprinting, however, is a separate, learned technique that often requires specific feedback. When attempting maximal speed, distance runners may benefit by focusing on one characteristic of technique. If knee extension at toe-off could be trained to become more sprint-like, the other characteristics unique to sprinters may follow.